Evaluating the food consumption among Indonesian young adults lived in a different environment - Rany Adelina; Esti Nurwanti; Rathi Paramastri; Carissa Cerdasari; Jane C J Chao (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Indonesian young adults who live abroad usually buy meals from café or catering. These meals tend to be less nutritious, including high fat, low fiber, and high carbohydrate.Objective: This study aimed to investigate the pattern of food consumption among young Indonesian adults who lived in a different environment.Materials and Methods: A cross-sectional observational study was carried out with 497 participants (73 men and 420 women). Data were collected using a validated food frequency questionnaire (FFQ) of 78 food groups. In addition, the Mann-Whitney U test was conducted to compare consumption patterns among study participants who lived in a different environment (Malang city, East Java, Indonesia, and Taipei City, Taiwan). Furthermore, the Chi-Square test and Fisher’s exact test analyzed the consumption level by gender.Results: Our study indicated no significant differences between food consumption of Indonesian young adults in Malang city, Indonesia, and Taipei City, Taiwan (p=0.623). Meanwhile, beverage (tea) was significantly different between gender in the home country (p=0.005). In contrast, participants who lived abroad showed significantly different consumption levels of fast food (instant noodle) and plant protein source (tofu) across gender (p=0.01 and p=0.02).Conclusion: The present study showed that fruits were often changed into juices, especially more frequent in a home country than abroad. Meanwhile, several food items, including beverages (tea), fast food, and plant protein source (tofu), showed significant differences across gender.